Distributions of chlorinated paraffins and the effects on soil microbial community structure in a production plant brownfield site. (July 2020) - Wu, Yingxin; Wu, Jiahui; Tan, Haijian; Song, Qingmei; Zhang, Jie; Zhong, Xi; Zhou, Jingyan; Wu, Wencheng; Cai, Xinde; Zhang, Weihua; Liu, Xiaowen
Abstract: The distributions of chlorinated paraffins (CPs) in soils and their ecological effects attract much attention, while site-scale data are still scarce. In this study, a comprehensive investigation was performed to understand the CP distributions at a CP production plant brownfield site, as well as their effects on soil microbial community. Short-, medium- and long-chain CPs (SCCPs, MCCPs, LCCPs) were detected in most samples with total contents ranging ND-5, 090, ND-6, 670, and ND-1450 ng g −1 (dw), respectively. A CP-hotspot was observed 10 m beneath the synthesis workshop, indicating the downward migration of CPs. The consistence of soil SCCP congener profiles with commercial product CP-52 suggested the leakage of CP products as the contamination source. Besides CPs, petroleum hydrocarbons (PHC) contamination also occurred beneath the synthesis workshop. Soil microbial community composition and diversity were significantly influenced by SCCPs (p < 0.05) despite their lower contents compared to other concerned contaminants. Microbial network analysis indicated nonrandom co-occurrence patterns, with Acinetobacter, Brevibacterium, Corynebacterium, Microbacterium, Stenotrophomonas, and Variibacter as the keystone genera. Genera from the same module showed significant ecological links (p < 0.05) and were involved in the degradation of PHCs and chlorinated organic contaminants. This study provides the first phylogenetic look at the microbial communities in CP contaminated soils, indicating that the long-term exposure to CPs and PHCs may lead to microbial group assemblages with the potential for degradation. Graphical abstract: Image 1 Highlights: Effects of CPs on soil microbial community structures were studied for the first time. Co-contamination of CPs and PHCs was induced by CP synthesis. Hotspot distribution and downward migration of CPs, specially SCCPs, were observed. SCCPs shaped the soil microbial community composition and co-occurrence network. Soil microbial community from the site offers potential to degrade CPs and PHCs. Abstract : SCCPs shaped the soil microbial community composition and co-occurrence network that offers potential to degrade CPs and PHCs.